WorldSciNet
WorldSciNet provides online access to a total of 68 journals in full text in downloadable PDF files published by World Scientific in subject areas such as : nanotechnology, biomedical science and computational science. Recently, the scope was broadened to include materials science, medical science, life sciences, banking and finance, and business management. Starting from 2001, the electronic versions are available free to institutional subscribers of their printed versions.